Efektivitas Video Pembacaan Puisi dalam Memahami Isi Puisi Siswa Kelas VII SMP Negeri 7 Cilacap Tahun 2025 - Wuri Handayani; Eko Suroso (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Learning to Understand the Content of Recited Poetry is a crucial aspect of literature instruction at the junior high school level. However, field observations indicate that many students struggle to appreciate poetry due to its imaginative and multi-interpretative language (Afiana et al., 2022). This study aims to improve the skill of understanding poetry content through the implementation of a modeling-based learning model using poetry recitation videos for seventh-grade students at SMP Negeri 7 Cilacap. This research adopts a quantitative approach, with subjects consisting of seventh-grade students selected based on their initial achievement, which did not meet the standard of learning mastery. The instruments used include a poetry comprehension skills test and non-test instruments such as observation, interviews, journals, and documentation. The data were analyzed using both descriptive quantitative and qualitative methods. The results indicate that the modeling learning model combined with poetry recitation videos significantly enhanced students' ability to understand the content of poetry. The average score increased from 74.78 to 78.6, exceeding the Minimum Mastery Criteria (KKTP). Improvements were observed in the ability to identify the theme, message, feeling, tone and atmosphere, as well as in the ability to summarize the overall content of the poem. Additionally, there was a positive change in student behavior, with learners becoming more active, confident, and enthusiastic during the learning process. The video presentations played an important role in enthusiastic during the learning process. The video presentations played an important role in stimulating students’ auditory perception and imagination (Arlindo et al., 2022), while the modeling approach encouraged both cognitive and affective engagement (Musfiroh & Kanzunnudin, 2022). These findings affirm that instructional strategies integrating inductive approaches and audio-visual media are effective in enhancing students’ literary appreciation competencies (Sayoga & Nurlatifah, 2023). This study provides practical insights for teachers in designing engaging and effective poetry lessons and recommends further research to examine the effectiveness of similar strategies in broader educational contexts (Utomo et al., 2023).